2009
DOI: 10.1002/j.0022-0337.2009.73.3.tb04706.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Pediatric Dental Program Directors’ Selection of Residents and Demographics of Current Directors

Abstract: The primary goal of this study was to examine the criteria that influence rankings of candidates by advanced education program directors in pediatric dentistry. Secondary objectives were to obtain information on the resident selection process and to explore demographics of current program directors. A survey was sent in 2005 to all sixty-three program directors of pediatric dentistry residency programs accredited within the United States for the graduating class of 2007. The survey had a response rate of almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 27 publications
2
30
1
Order By: Relevance
“…18,19 This study's results demonstrated that the other parts of application increased in importance and in similar rank order as compared to 2005. 2 However, the applicant's essay is higher in the rank order in 2018 than in 2005. This is important to note since it is a nonobjective measure that has increased in importance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…18,19 This study's results demonstrated that the other parts of application increased in importance and in similar rank order as compared to 2005. 2 However, the applicant's essay is higher in the rank order in 2018 than in 2005. This is important to note since it is a nonobjective measure that has increased in importance.…”
Section: Discussionmentioning
confidence: 99%
“…Majewski et al previously found that pediatric dentistry program directors valued National Board scores, dental school clinical grades, class rank, and GPA during the application process. 2 However, the Joint Commission on National Dental Examinations began to report National Board Dental Examination scores as pass/fail after January 1, 2012. [13][14][15] Therefore, the previously most important factor is not available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to dental school admissions, postdoctoral programs assess advanced education applicants based on a combination of cognitive and noncognitive factors. Cognitive assessments include dental school rank, GPA, and performance on standardized testing specific to the residency, while noncognitive assessments include the interview and letters of recommendation 12 . With some dental specialties heavily weighted towards specific personality types, 13 , 14 there exists a potential correlation between noncognitive elements of the predoctoral application and placement in a residency program, although this correlation has yet to be studied.…”
mentioning
confidence: 99%